Conceitos de contabilidade e suas relações com a estrutura conceitual básica, com a formação docente e rendimento discente - Lames, Edilei Rodrigues de (2019)
The past two decades have been marked by discussions, adjustments, and changes in accounting that have resulted in the adoption of global accounting standards through the implementation of IFRS (International Financial Reporting Standards). Initiated in the European Union and adopted by Brazil in 2007, this process already has membership of more than 140 countries. This is a historic milestone for accounting, which, in a short time now has a Conceptual Framework and accepted standards in 73% of the world's countries. The advances are significant, however, accounting theory still lacks discussion and deepening, lacking a widely accepted international accounting concept, or at least consistent and adopted by the Conceptual Framework for Financial Reporting. Accounting, throughout history, has been conceptualized in different ways, such as method, technique, art, historical record, service activity, commodity, information system, representation of reality, among others. Considering the lack of definition and adoption of an accounting concept by the Conceptual Framework, as well as the sparse discussion about the limitations of accounting and the lack of implications for teaching and student performance, the aim of this study is to evaluate the impact of the understanding that Teachers have the concept of Accounting with limitations and basic Conceptual Structure, teacher training and student achievement. The Delphi technique was used to validate the limitations inherent in the concept of accounting as a representation of reality and the qualitative characteristics of useful financial accounting information. Subsequently, questionnaires were applied to 650 accounting science teachers in Brazil, after approval by the ethics committee under No. 2,952,702. Data analysis was performed using descriptive statistics, correlation tests, confidence intervals, logistic regression, and, beta regression. The results indicate a consensus between the results of Delphi and the teachers surveyed, as well as the existence of coherence and alignment between the concept of accounting as a representation of reality and the conceptual framework. The acceptance of the attributes (limitations) of this concept by the teachers, previously validated by the Delphi expert committee, is confirmed. The results also show evidence of positive implications for student achievement (CFC Sufficiency Exam) but are still fragile and lacking in depth. The results suggest the need to foster discussion by stricto sensu graduate programs to deepen the understanding of limitations and contribute, wherever possible, to overcome them. They also signal the need to rethink elements of the political-pedagogical project, especially for the necessary realignment as to the accountant's profile and skills. The study contributes to the systematization of the limitations of accounting and the choice of a concept that can be used by the basic Conceptual Framework, the concept of Accounting as a Representation of Reality, by the evidence of its alignment with the Conceptual Framework, besides bringing reflections on the definition. of concept.